Podcasting New Aural Cultures and Digital Media (Springer International Publishing, 2018)
Podcasting: New Aural Cultures and Digital Media is the first comprehensive interdisciplinary collection of academic research exploring the definition, status, practices and implications of podcasting through a Media and Cultural Studies lens. By bringing together research from experienced and early career academics alongside audio and creative practitioners, the chapters in this volume span a range of approaches in a timely reaction to podcasting's zeitgeist moment. In conceptualizing the podcast, the contributors examine its liminal status between the mechanics of 'old' and 'new' media and between differing production contexts, in addition to podcasting's reliance on mainstream industrial structures whilst retaining an alternative, even outsider, sensibility. In the present tumult of online media discourse, the contributors frame podcasting as indicative of a 'new aural culture' emerging from an identifiable set of industrial, technological and cultural circumstances. The analyses in this collection offer a range of interpretations which begin to open avenues for further research into a distinct Podcast Studies.